2018
DOI: 10.1123/japa.2017-0213
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity Among Middle-Aged and Older Adults With Hazardous Drinking Habits in Six Low- and Middle-Income Countries

Abstract: We investigated physical activity (PA) correlates among middle-aged and older adults (aged ≥50 years) with hazardous drinking patterns in six low- and middle-income countries. Cross-sectional data were analyzed from the World Health Organization's Study on Global Ageing and Adult Health. Hazardous drinking was defined as consuming >7 (females) or >14 (males) standard drinks per week. Participants were dichotomized into low (i.e., not meeting 150 min of moderate PA/week) and moderate-high physically active grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…With the rapid urbanization and progressive urban densification particularly in LMICS and the observation that physical inactivity is particularly high in urban residents in LMICs [38][39][40] , present findings suggest that built environment strategies may be effective physical and mental health promotion strategies in LMICs. Future studies should examine whether providing improved access to outdoor recreation spaces, informal places to walk, and well-maintained sidewalks could result in more physical activity uptake, less sedentary behavior and consequently mental and physical health improvements.…”
Section: Discussionmentioning
confidence: 75%
“…With the rapid urbanization and progressive urban densification particularly in LMICS and the observation that physical inactivity is particularly high in urban residents in LMICs [38][39][40] , present findings suggest that built environment strategies may be effective physical and mental health promotion strategies in LMICs. Future studies should examine whether providing improved access to outdoor recreation spaces, informal places to walk, and well-maintained sidewalks could result in more physical activity uptake, less sedentary behavior and consequently mental and physical health improvements.…”
Section: Discussionmentioning
confidence: 75%
“…Future research should explore why unemployment, for example, due to retirement, is an influential factor in the association between physical activity and loneliness in these two countries. At least, it is known that middle‐aged and old‐age people in LMICs who are employed are more physically active . Speculatively, employment may offer opportunities for social connection, enhance social functioning, and, consequently, provide more opportunity to be active, to feel as a meaningful contributor to society, and to feel less lonely …”
Section: Discussionmentioning
confidence: 99%
“…At least, it is known that middle-aged and old-age people in LMICs who are employed are more physically active. 48,49 Speculatively, employment may offer opportunities for social connection, enhance social functioning, and, consequently, provide more opportunity to be active, to feel as a meaningful contributor to society, and to feel less lonely. [50][51][52] Social cohesion was a particularly strong confounder in Russia.…”
Section: General Findingsmentioning
confidence: 99%
“…Not having a job was an independent predictor. In previous research in people with mental health disorders in LMICs, [37][38][39] it has been demonstrated that those who are employed are more likely to be physically active. Speculatively, employment is not only physically demanding but may also offer opportunities to connect socially, enhance social functioning, and consequently have more opportunity to be more active, to feel an active contributor to the society, and to feel less lonely.…”
Section: General Findingsmentioning
confidence: 99%